The Bankers - Mayer, Martin (New York : Weybright and Talley, 1974)
The book provides insights to banking as a business and explained some of the macroeconomics principles, policies and standard that are applicable to banks.
Includes index
Includes bibliographic references
osc 02/06/17
Loans
Keywords: Banks and banking; Federal Reserve banks; Financial services industry; United States; Europe